The Celluloid Specimen : Moving Image Research Into Animal Life - Benjamin Schultz-Figueroa (University of California Press, 2023)
A free ebook version of this title is available through Luminos, University of California Press's Open Access publishing program. Visit www.luminosoa.org to learn more. In The Celluloid Specimen, Benjamín Schultz‑Figueroa examines rarely seen behaviorist films of animal experiments from the 1930s and 1940s. These laboratory recordings—including Robert Yerkes's work with North American primate colonies, Yale University's rat‑based simulations of human society, and B. F. Skinner's promotions for pigeon‑guided missiles—have long been considered passive records of scientific research. In Schultz‑Figueroa's incisive analysis, however, they are revealed to be rich historical, political, and aesthetic texts that played a crucial role in American scientific and cultural history—and remain foundational to contemporary conceptions of species, race, identity, and society.